1994
DOI: 10.1111/j.1365-2265.1994.tb02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid status on thyroid autoimmunity expression in euthyroid and hypothyroid patients with Hashimoto's thyroiditis

Abstract: This study demonstrates that thyroid status can modulate thyroid autoimmunity expression, such as TSH-RAb and TPOAb, in patients with euthyroid or hypothyroid goitrous Hashimoto's thyroiditis. Similar results have been reported in patients with Graves' disease made euthyroid by the administration of thyroid hormone during antithyroid drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 37 publications
1
33
1
Order By: Relevance
“…This may be important since patients with diffuse goiters and HT respond well to suppressive therapy with thyroxine. 9 Rieu et al 10 report that in Hashimoto's thyroiditis, levothyroxine therapy decreases the titers of some circulating thyroid autoantibodies but long-term follow-up studies with thyroxine therapy would be required to see if decreasing antibody titers would lead to clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…This may be important since patients with diffuse goiters and HT respond well to suppressive therapy with thyroxine. 9 Rieu et al 10 report that in Hashimoto's thyroiditis, levothyroxine therapy decreases the titers of some circulating thyroid autoantibodies but long-term follow-up studies with thyroxine therapy would be required to see if decreasing antibody titers would lead to clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism behind this effect of T 3 could be stimulation of an already ongoing immune process at this age. The biphasic time-dependent effect of T 3 on the prevalence of thyroiditis may reflect the dilemma of whether or not treatment with thyroid hormones might enhance an ongoing immune process of human autoimmune thyroiditis (9,10).…”
Section: Body Weight (G) (Mean^sem) (N)mentioning
confidence: 99%
“…In humans, the influence of thyroid status on thyroid autoimmunity is controversial (9,10). However, the comparable pathogenetic mechanisms of AIT and T1DM and the reduction in the incidence of T1DM by changed b-cell activity (11 -13) caused us to examine whether changed thyroid activity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A 1-year controlled study of thyroxine therapy in both euthyroid and hypothyroid HD patients found that thyroid antibody levels decreased in both subject groups 24 . The thyroxine effects on thyroid function and its status were interpreted as having modulated autoimmunity expression in HD 23,24 .…”
Section: Hypothesis Raised: Could Thyroxine Treatment Diminish Risk Omentioning
confidence: 99%
“…The thyroxine effects on thyroid function and its status were interpreted as having modulated autoimmunity expression in HD 23,24 . The prophylactic effect of levothyroxine therapy in euthyroid HD patients was tested in a controlled 1-year study of 10 treated versus 11 untreated patients 25 .…”
Section: Hypothesis Raised: Could Thyroxine Treatment Diminish Risk Omentioning
confidence: 99%